Biological Effects of Newcastle Disease Virus Vaccine on Colon Cancer Cells line (HCT116) - Hamzah, Alaa Halos (Medical Science Journal for Advance Research, 2026)
Background: Newcastle disease virus (NDV) is a type of avian paramyxovirus that has demonstrated its ability to selectively replicate in tumor cells and also stimulate an anti-tumor immune response, making it a potential oncolytic agent. Therapeutic efficacy of NDV in colorectal cancer has yet to be analyzed. Objective: The aim of this study was to assess the oncolytic activity of NDV vaccine strains in colon cancer cell line HCT116 in terms of cytotoxicity, induction of apoptosis, alterations in metabolism, and viral replication. Methods: HCT116 cells were infected with NDV vaccine strains at different MOI (1 and 10) and time points (48 and 72 hours post infection) and analyzed. Cell viability was assessed with an MTT assay, and apoptosis was analyzed with Annexin V-FITC/PI flow cytometry. The presence of cytopathic effects was assessed microscopically. Glucose metabolism and lactate production, ATP levels, and viral replication (by means of the hemagglutination assay) were assessed. Results were presented as mean ± SD (n=3) and analyzed using one-way and two-way ANOVA with post hoc Tukey comparison. Results: NDV significantly decreased HCT116 cell viability in a dose and time dependent manner (p < 0.0001) with cell viability at 32% at MOI 10 and 72 hours post infection. There was also a significant increase in apoptosis, including early apoptosis which was 32.8%, and in the case of late apoptosis/necrosis which was 41.2% at MOI 10 (p < 0.0001). NDV also caused significant cytopathic effects and in metabolism of the cells as evidenced by decreased glucose consumption (49%), lactate production (47%), and ATP levels (52%) (p < 0.001). There was a positive correlation between the increased time of viral replication and increase in cytotoxicity (p = 0.0001). Conclusion: NDV vaccine strains were shown to effectively elicit oncolytic activity against HCT116 colon cancer cells via apoptosis, suppression of metabolism, and viral replication. These results advocate for Newcastle Disease Virus (NDV) as a potential novel approach for targeted therapy in colorectal cancer.